MINIMIZE THE HYDROGENATION OF UNSATURATED FATTY ACID IN RUMEN WITH FORMALDEHYDE - Nafly C. Tiven; Lies Mira Yusiati; Rusman Rusman; Umar Santoso (Universitas Gadjah Mada, 2011)
This research aimed to know the ability of formaldehyde to protect unsaturated fatty acid of CPO on the hydrogenation process by rumen microbes. In this experiment, the in vitro fermentation of rumen fluid was carrying out. It was taken from the rumen-trocar of female sheep. The unsaturated fatty acid source was from CPO (Crude Palm Oil) which encapsulated by formaldehyde 37% within 0%, 1%, 2% and 3%. The data was analyzed by Completely Random Design with Duncan's New Multiple Range Test. The difference of means the treatments were tested by Duncan's New Multiple Range Test. Result showed that oleic and linoleic resulting from fermenting CPO protected by formaldehyde was increase if it was compared with the unprotected CPO. It can be concluded that encapsulated CPO with formaldehyde was able to prevent hydrogenating of unsaturated fatty acid, mainly oleic and linoleic.